Legal implications in routine clinical practice - Nadesan, Kasinathan; Nambiar, Phrabhakaran; Swaminathan, Nambiar Dasan (Faculty of Medicine, University of Malaya, 1999)
Medico-legal management forms an important part of the total patient care. With the rapid progress of medical science and technology, the law and ethics pertaining to clinical practice have become more complicated in order to meet the various complex issues that have arisen. Medical ethics is a code of behavior accepted voluntarily within the profession, as opposed to statutes and regulations that are imposed by official legislation. Much of medical ethics consists of good manners and civilized behavior in the general sense, but there are certain matters, which are particular to the practice of the profession of medicine. Matters of immediate concern in routine clinical practice are pertaining to consent, confidentiality and negligence.